Restructuring the Supply Chain in the Post Covid Era with Geopolitics in the Background - Vikas Gupta (ExcelingTech, 2022)
Over the last decade, the topic of supply chain disruptions has increasingly gained importance among scholars and professionals due to changing business dynamics and several developments on the geopolitical front. The U.S.-China trade war has developed an overall geopolitical trend in favor of nationalization followed by the recent COVID-19 pandemic, which altered the priorities of several supply chain leaders who now have to balance operational efficiency and cost alongside building greater resilience of the supply chain. Several articles and other literatures have been published in important journals and other public domains which form the basis of our study. The emphasis is on restructuring of supply chain in the post-Covid era in the backdrop of recent geopolitical mayhem. The Russian invasion of Ukraine and the resultant sanctions imposed on Russia and the recent Covid-19 lockdowns in China are latest events which have played havoc with the worldwide supply chains. Important studies on this subject, have been acknowledged and evaluated, based on reviews. Detailed evaluation of these studies scrutinized existing information regarding the various types of disruptions, their effect on supply chains, the flexibility in-built in supply chain design and the strategies for recovery, supported by cost-benefit calculations, are recommended by the studies. Research on supply chain in the context of COVID-19 is still in the nascent stages. This article contributes to the development of literature on the subject.